Development of novel vaccines against human cytomegalovirus. Issue 11 (2nd November 2019) - Cui, Xinle; Snapper, Clifford M.
ABSTRACT: Congenital human cytomegalovirus (HCMV) infection and HCMV infection of the immunosuppressed patients cause significant morbidity and mortality, and vaccine development against HCMV is a major public health priority. Efforts to develop HCMV vaccines have been ongoing for 50 y, though no HCMV vaccine has been licensed; encouraging and promising results have obtained from both preclinical and clinical trials. HCMV infection induces a wide range of humoral and T cell-mediated immune responses, and both branches of immunity are correlated with protection. In recent years, there have been novel approaches toward the development of HCMV vaccines and demonstrated that vaccine candidates could potentially provide superior protection over natural immunity acquired following HCMV infection. Further, rationally designed HCMV protein antigens that express native conformational epitopes could elicit optimal immune response. HCMV vaccine candidates, using a multi-antigen approach, to maximize the elicited protective immunity will most likely be successful in development of HCMV vaccine.